i need some help please with the following equation, I need to make c the subject of z=sqrt(r^2 + (xl - xc)^2).
My first step was remove the sqrt to become z^2=r^2 + (xl - xc)^2
Then expand the brackets so z^2=r^2 + (xl - Xc)(Xl -Xc)
then Multiply out the brackets so z^2 = r^2 + xl^2 - xc^2 - 2xlxc
then I'm a bit stuck where to go from there. I could move the r^2 to the other side but I'm still none the wiser on getting c as the subject.
i was also given xl= 2(pi)fl and xc = 1/ 2(pi)FC
z=104ohms r=100ohms f=50hz, l= 0.1 henry
any enlightenment would be greatly appreciated!